2015
DOI: 10.1093/ntr/ntv169
|View full text |Cite
|
Sign up to set email alerts
|

Acute Exposure to Electronic and Combustible Cigarette Aerosols: Effects in an Animal Model and in Human Alveolar Cells

Abstract: Despite higher exposure conditions, ECIG exhibited less toxic effects on lungs of experimental animals and on A549 cell cultures when compared to CS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
104
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(113 citation statements)
references
References 16 publications
7
104
0
2
Order By: Relevance
“…305 Particular ENDS flavors are more cytotoxic than others, but generally most studied ENDS liquids are much less cytotoxic than cigarette smoke extract. 213,228,238,250,254,260,295,296,308 In cytotoxicity studies, cinnamon flavor in ENDS was found to be the most toxic (i.e., inhibiting cell survival or inducing cell stress/morphologic change) when comparing flavors. 198,247 Most studies find that nicotine levels are not correlated with cytotoxicity.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…305 Particular ENDS flavors are more cytotoxic than others, but generally most studied ENDS liquids are much less cytotoxic than cigarette smoke extract. 213,228,238,250,254,260,295,296,308 In cytotoxicity studies, cinnamon flavor in ENDS was found to be the most toxic (i.e., inhibiting cell survival or inducing cell stress/morphologic change) when comparing flavors. 198,247 Most studies find that nicotine levels are not correlated with cytotoxicity.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Recent studies have found that exhaled ecigarette aerosol contains nicotine, propylene glycol, glycerol, particulate matter, ultra-fine particles, and VOCs [14][15][16]. Another study found that exposure to the secondhand aerosol was associated with an increase in serum cotinine levels similar to traditional cigarette smokers [17]. The large number of people using e-cigarettes indoors at vaping conventions may increase health risks among attendees and convention workers.…”
Section: Intoductionmentioning
confidence: 99%
“…Increased IL-6 levels are associated with increased severity and persistence of joint pain (4). Notably, cigarette smoke extract in non-cytotoxic doses is capable of increasing the levels of IL-6 in cell cultures (28) and in animal models (29). Additionally, smoking correlates with higher serum levels of IL-6 in apparently healthy individuals, the elderly and HIV-infected patients (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%